Use of Risk Assessment Tool for Inpatient Traumatic Intracranial Hemorrhage after Falls in Acute Care Hospital Setting - Toyabe, Shin-ichi (Glob J Health Sci, 2012)
Severe injuries such as intracranial hemorrhage (ICH) are the most serious problem after falls in hospital, but they have not been considered in risk assessment scores for falls. We tried to determine the risk factors for ICH after falls in 20,320 inpatients (696,364 patient-days) aged from 40 to 90 years who were admitted to a tertiary-care university hospital. Possible risk factors including STRATIFY risk score for falls and FRAX™ risk score for fractures were analyzed by univariate and multivariate analyses. Fallers accounted for 3.2% of the patients, and 5.0% of the fallers suffered major injuries, including peripheral bone fracture (59.6%) and ICH (23.4%). In addition to STRATIFY, FRAX™ was significantly associated not only with bone fractures but also ICH. Concomitant use of risk score for falls and risk score for fractures might be useful for the prediction of major injuries such as ICH after falls.